2011
DOI: 10.1016/j.radonc.2011.05.064
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the molecular pathology of radiation-induced pneumopathy

Abstract: CitationNew insights into the molecular pathology of radiationinduced pneumopathy. Background and Purpose: Pneumonitis and fibrosis constitute dose-limiting side effects of thorax

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 27 publications
2
79
0
Order By: Relevance
“…It is generally accepted that blood vessels are critical components of the radiation response and that vascular damage upon irradiation is particularly prominent in the radiation response of normal tissues (9,25,31,44,84). We and others showed that thorax irradiation results in impairment of various pulmonary vascular parameters such as structural changes in pulmonary …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is generally accepted that blood vessels are critical components of the radiation response and that vascular damage upon irradiation is particularly prominent in the radiation response of normal tissues (9,25,31,44,84). We and others showed that thorax irradiation results in impairment of various pulmonary vascular parameters such as structural changes in pulmonary …”
Section: Discussionmentioning
confidence: 95%
“…We and others showed in preclinical studies that radiationinduced normal tissue toxicity in the lung is closely linked to vascular EC damage and dysfunction of the blood-air barrier (9,25,31,84). However, the underlying mechanisms of radiationinduced adverse late effects are still not well understood, and no causative radioprotective treatment is available to date.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, Rexo2 is an RNA exonuclease and recently another similar enzyme, Xrn2 has been associated with murine lung cancer [19] through its involvement in epithelial cell proliferation. Impaired restoration of the alveolar epithelium following the initial stimulus is a potential trigger for pulmonary fibrosis [40,41], therefore variation in a gene implicated in alveolar cell proliferation could contribute to radiation-induced lung damage.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this, Ddr1 -/-mice have been shown to develop a reduced amount of pulmonary fibrosis in response to a related challenge, that of bleomycin-induced lung injury [44], and in separate work [45], to be protected from renal fibrosis. An inflammatory contribution to the tissue response of fibrosis has also been suggested [46] and polymorphisms within particular candidate genes which function to alter the inflammatory response (Slamf6, Btnl1) could thus affect susceptibility to radiation-induced lung disease [41,47,48]. Further, increased levels of the cytokine transforming growth factor beta (Tgf-β) in lung tissue have been implicated in the development of fibrosis in animal models [49], including in response to irradiation [50] and specific candidate genes identified in our analysis (Cdkn1a or p21, Pin1) have been demonstrated to influence fibrosis development by altering Tgf-β levels [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Radiation-induced lung injury (RILI) is a common complication of radiotherapy and a key dose-limiting factor, which may reduce the probability of tumor control and affect the patient's quality of life (1). The pathology of RILI is complex, and includes radiation-induced pneumonitis and fibrosis (2). Although intensive study in the previous decades has elucidated a number of the associated underlying mechanisms, involving, for example, cells and cytokines, the specific mechanism remains unclear (3).…”
Section: Introductionmentioning
confidence: 99%